ANALISIS YURIDIS PERTIMBANGAN HUKUM HAKIM TENTANG PERMOHONAN PERUBAHAN NAMA ORANG TUA PADA AKTA KELAHIRAN ANAK DI DALAM PENETAPAN NOMOR 287/PDT.P/2023/PN.MPW - NIM. A1012191207, JAKA SUMA TRIYUDA (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractIn submitting a name change application to the local District Court by citizens who wish to change their name, the process is not easy to obtain approval for a name change determination by the District Court. So the judge, through his decision on several applications to change his name, apart from accepting the application, the judge also rejected it, which resulted in the cancellation of citizens who wanted to change their name. Various reasons, both juridical (legal), sociological and philosophical, have been very well established by district court judges. This sometimes results in not being able to find common ground as to why the application for a personal name was rejected, seen in the two decisions, namely, the Mempawah District Court's decision Number 287/Pdt.P/2023/PN Mpw.So the formulation of the problem in this study is